Forest vegetation analysis of several altitudes in Wawouwai hill, Wawonii Island, Southeast Sulawesi - PURWANINGSIH PURWANINGSIH (Society for Indonesian Biodiversity, 2006)
Study on forest vegetation at some different altitudes in Wawouwai hill, Wawonii Island, Southeast Sulawesi had been carried out by using quadrate method. The sampled plots were 100 m, 300 m and 500 m asl. The aims of this research were to know the species composition and forest structure of the reserve forest remain in Wawonii Island. Based on analyzed data from the three plots, it has been recorded totally 88 species plants belong to 70 genera and 39 families. Dominant species on each plot was different. The dominant species in plot I were Palaquium obovatum, Polyalthia sp., Santiria laevigata, and Garcinia sp. The dominant species in plot II were Kjellbergiodendron celebicum, Baccaurea javanica, Santiria laevigata, and Calophyllum soulatri. Xanthostemon confertiflorum, Podocarpus neriifolius, Garcinia celebica and Gulubia sp. were dominant species in plot III. Forest structure was reflected by tree height and diameter classes. Forest structure usually was catagorized in strata B ( 30 m high were still found, however in plot III most of trees had a small diameter and occupied strata C (< 10 m high). Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: vegetation, forest, altitude, Wawonii, Southeast Sulawesi